Relación entre la Lactancia Materna, Artificial y Mixta con el Crecimiento Mandibular en Niños de 0 a 6 Meses de Edad Atendidos en el Centro de Salud la Esperanza. Tacna, 2017 - Ayca Castro, Isabel Del Rosario (2018)
El estudio de investigación titulado: Relación entre la lactancia materna y artificial con el crecimiento mandibular en niños de 6 meses de edad atendidos en el Centro de Salud la Esperanza. Tacna, 2017, tiene como objetivo el de determinar la relación que existe entre la Lactancia materna y artificial con el crecimiento mandibular en niños de 6 meses de edad y establecer las semejanzas y/o diferencias entre la lactancia materna y artificial. Tiene como variables: el crecimiento mandibular y la lactancia. La hipótesis planteada refiere la probabilidad de que en los niños de 0 a 6 meses de edad que se alimentan con lactancia materna tengan un crecimiento mandibular normal en relación los niños alimentados con lactancia artificial. The research has taken 26 children of 6 months of age: 14 fed with lactation and 12 with artificial lactation selected through the inclusion and exclusion criteria. The conclusions reached are: 1) The average and maximum and minimum values of the Mandibular Growth of the 6-month-old children fed with breastfeeding, with the GO-GN levels; GO-GO; GO-STN and TG-GN is 74.73 mm; 101.13 mm; 38.78 mm and 94.00 mm, respectively. 2) The mean and maximum and minimum values of the Mandibular Growth of the 6-month-old children fed with breastfeeding, with the GO-GN levels; GO-GO; GO-STN and TG-GN is 70.75 mm; 92.13 mm; 36.83 mm and 88.33 mm, respectively. 3) Compared the results of the means of both groups of 6-month-old children investigated a difference in mandibular growth was observed: higher in children fed exclusive breastfeeding and lower in children fed with artificial lactation and 4) Breastfeeding contributes notably the correct growth and development of the buccal apparatus, favoring muscular action through the suction and swallowing of breast milk and the proper positioning of the jaw, in the transversal growth of the jaws, facilitates the development of dental occlusion. Palabras claves: Lactancia materna y artificial – crecimiento mandibular